Transcatheter Aortic Valve Implantation in Sievers Type 0 vs. Type 1 Bicuspid Aortic Valve Morphology: Systematic Review and Meta-Analysis - Du, Yu; Wang, Zhijian; Liu, Wei; Guo, Yonghe; Han, Wei; Shen, Hua; Jia, Shuo; Yu, Yi; Han, Kangning; Shi, Dongmei; Zhao, Yingxin; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2021)
Background Transcatheter aortic valve replacement (TAVR) has achieved satisfactory outcomes in selected patients with bicuspid aortic valve (BAV), predominately type 1 BAV (~90%). Less is known about safety and efficacy of TAVR in type 0 BAV. This study aims to compare procedural and 30-day outcomes after TAVR between type 0 and type 1 BAV. Methods Studies comparing outcomes of TAVR in Sievers type 0 vs type 1 BAV were sought from PubMed, EMBASE, Cochrane Library, and Web of Science from inception to May 2021. Data was extracted on study characteristics and outcomes. Odds ratio (OR) with 95% confidence interval (CI) were pooled for procedural and 30-day outcomes. Results Six observational studies were included with determined type 0 BAV in 226 patients and type 1 BAV in 902 patients. In pooled analyses, incidence of death (OR=1.22; 95% CI 0.48-3.10), stroke (OR=0.54; 95% CI 0.13-2.36), new pacemaker (OR=0.64; 95% CI 0.18-2.23) at 30 days were not significantly different between these 2 BAV morphologies (all p>0.05). Similarly, compared to type 1 BAV, patients with type 0 BAV had similar incidence of device success (OR=0.62; 95% CI 0.29-1.32), ≥ mild paravavular leak (OR=0.83; 95% CI 0.43-1.60), conversion to surgery (OR=3.36; 95% CI 0.45-25.27), whereas significantly higher risk of coronary compromise (OR=7.18; 95% CI 1.48-34.88). Heterogeneity of treatment effect across the studies for these outcomes were low. Conclusions Patients with type 0 BAV seem to have similar procedural and 30-day outcomes after TAVR in comparison with type 1 BAV.